SEEDS ECOPHYSIOLOGY IN AN ALTITUDE MARSH IN PARAIBA STATE, BRAZIL, AIMING THE CONSERVATION OF THE AUTOCHTHONOUS BIODIVERSITY - Silva de Medeiros, Robson Luis [UNESP]; Souza, Venia Camelo de; Barros Santos, Jose Nailson; Azeredo, Gilvaneide Alves de; Anjos, Fabiana dos (Centro Pesquisas Florestais, Ufsm, 2017)
The altitude swamps in northeast Brazil are areas with divergent microclimates from the context that theyare located, their forest formations are disjunctions of the Atlantic Forest, marooned by the 'Caatinga' vegetation, a condition that makes these remaining areas with high biodiversity. Botanical research in remnants forests of Paraiba state, particularly with regard to the redemption of germplasm, are relevant. The aim of this study was to evaluate the ecophysiology of seeds from native species of the Fabaceae family selected in the CCHSA forest fragment, submitted to thermal stress and monitor their reproductive phenophases. The experiment was conducted at the Seed Laboratory of the CCHSA/UFPB and with the aid of B.O.D germinators, with 8 hours of photoperiod in a randomized experiment design with constant temperatures of 20, 25, 30 and 40 degrees C. The seeds were distributed on a paper towel moistened with distilled water equivalent to three times the weight of the dry paper. Four replicates of 25 seeds were used per treatment. Data of germination and Germination Speed Index (GSI) were submitted to analysis of variance and polynomial regression. The germination of Pterogyne nitens Tul. was affected by the studied temperatures and the temperature range that promoted higher germination percentage between 25 and 40 degrees C. The higher temperature (40 degrees C) markedly increased the germination and vigor of Senegalia tenuifolia L. Britton and Rose. The higher GSI was observed for Enterolobium contortisiliquum (Vell.) with the use of 40 degrees C of temperature. The results can indicate the optimum temperature and range temperature for germination and early seedling development of the species studied in its habitat.
Keywords: native forest seed; Atlantic Forest; abiotic factors